Reading strategy: Tackling reading through topic and main ideas - Naidu, Bharathi; Briewin, Marshal; Embi, Mohamed Amin (Canadian Center of Science and Education, 2013)
Reading comprehension is one of the four skills essential in learning English. In a reading class, students tend to read all the information provided in reading materials, but how much do they actually retain? This study explores whether learners use identification of the topic and main ideas as a reading strategy to assist in reading comprehension. The objective of this study is to enable learners to determine key concepts and main ideas in reading texts. By using this technique, learners will be able to get a clearer picture of what they are reading. A sample of 48 English as foreign language (EFL) learners from a private university in Malaysia participated in this study. The two instruments utilized in this study were grade interval and a self-reflection questionnaire. The findings confirmed an improvement in participant’s grades over pre- and post-reading assessments. Furthermore, the failure rate of the reading assessment decreased after the strategy was introduced. The results from this study will help instructors assist EFL learners in comprehending textual materials.